Graphical representation of statistical results in medical research - Salmelin, Raili (Acta Universitatis Tamperensis, ISSN 1455-1616, 1997)
Tiivistelmä.
Keywords: lääketiede; tilastot; graafinen esitys; diagrammit; ymmärrettävyys